Ethylene tetramerization catalyst composition and tetramerization method - WU HONGFEI; LIU JUN; WANG XIAOQING; LI TONGLIN; ZHENG MINGFANG; HAN CHUNHUI (2017)
The invention provides an ethylene tetramerization catalyst composition which comprises a ligand compound shown in formula I, a transition metal compound, a promoter and tert-butyl hydroperoxide, and in the formula, R and R' are identical or different and are independently selected from hydrogen, alkyl, alkoxy, cycloalkyl and halogen. The invention further provides an ethylene tetramerization method which comprises a step of performing ethylene tetramerization reaction in the presence of the ethylene tetramerization catalyst composition. 本发明提供了种乙烯四聚催化剂组合物，包括式I所示的配体化合物、过渡金属化合物、助催化剂和叔丁基过氧化氢；式中R和R'相同或不同，各自独立地选自氢、烷基、烷氧基、环烷基或卤素。本发明还提供了种乙烯四聚的方法，包括在所述的乙烯四聚用催化剂组合物的存在下，进行乙烯四聚反应。